The dynamic internationalization model of Slovenian born global SMES - Lejko, Ina (Management, 2013)
Small and medium sized enterprises (smes) are important business actors in the Slovenian, as well as European economy. In addition to the current global market conditions, reflecting a severe economic downturn, the smes in Slovenia and other transition economies operate under additional extensive external pressures, arising from the opening of their domestic markets. Under such conditions, companies, including smes, perceive internationalization as an inevitable, or even urgent step in the process of their business operations. However, companies pursue different paths in their internationalization efforts, one of them being a rapid internationalization strategy, denoted as the Born Global concept. In the paper, we explore the internationalization process of Slovenian Born Global smes. We employ an exploratory qualitative case study analysis of selected Slovenian smes in order to grasp the key characteristics of their internationalization process. On the basis of the latter we construct a dynamic internationalization model that might be used as a conceptual framework for empirical research of dynamic smes market behavior in Slovenia and other transition countries.
Keywords: mala podjetja; mednarodno poslovanje; Slovenia; Slovenija; srednja podjetja; tranzicija